The effect of group psychoeducational program on attitude toward mental illness in family caregivers of patients with bipolar disorder - Farnaz Rahmani; Hossein Ebrahimi; Fatemeh Ranjbar; Elnaz Asghari (Tehran University of Medical Sciences, 2016)
Background & Aim: Studies have shown that family caregivers' attitude toward mental illness affects their caring to mental patients and may reduce the quality of caring to them. This study aimed to determine the effect of group psychoeducation on attitude toward mental illness in the family caregivers of patients with bipolar disorder. Methods & Materials: In this randomized clinical trial study conducted in 2015, 74 family caregivers of the patients with bipolar disorder who had been hospitalized in the psychiatric wards of Razi hospital in Tabriz were selected by random sampling method. Then, they were randomly assigned into the experimental and control groups. The families of experimental group participated in 8 continuous 90-minute 2 times a week psychoeducational sessions. Family caregivers' attitude toward mental illness was measured using the questionnaire of Opinion about Mental Illnesses (OMI) before and after intervention. Data analysis was conducted using descriptive statistics, Chi-square test, independent t-test, paired t-test and ANCOVA on SPSS software version 13. Results: The results revealed that there was no significant difference in mean score of attitude toward mental illness between the experimental group and the control group before intervention (92.54±8.51 vs. 90.52±9.43, P>0.05). But the mean score of family caregiverschr('39') posttest in the experimental group significantly increased compared to the control group (105.43±14.72 vs. 90.52±7.50, P<0.05). Conclusion: The study results demonstrate that psychoeducational program improves family caregivers' attitude toward mental illness. Training methods such as group psychoeducation can be effective in promoting positive attitude in the families of patients with psychiatric disorder.